Systemic review of the literature of green supply chain management in the food packaging industry - Chumpitasi Ortigas, Renzo Ernesto (2023)
The awareness of green supply chain management (GSCM) has grown in the past year, particularly in the food packaging industry, due to population growth and its environmental impact. To explore this, we studied global perspectives on and contributions to GSCM, aiming to apply insights to developing countries. Our research revealed three main barriers hindering GSCM adoption in emerging economies: limited knowledge,inadequate technology, and high costs. By examining several authors’ viewpoints, we created a timeline showcasing GSCM’s evolution, enabling targeted improvements within the food packaging industry. Through this analysis, our paper not only reaffirms its initial objectives but also provides a foundation of tools and information for future GSCM research. This work contributes to the understanding of GSCM’s benefits and challenges, facilitating sustainable practices in a vital industry.